Xanthohumol protects against renal ischaemia reperfusion (I/R) injury by scavenging ROS and inhibition of JAK-2/STAT-3 inflammatory pathway. Issue 3 (1st May 2017) - Shati, Ali A.
Abstract: Recent evidence has shown that reactive oxygen species (ROS), inflammation and the activation of JAK/STAT signalling are major pathways in the induction and progression of renal ischaemia/reperfusion (I/R) injury. The protective effect of Xanthohumol (XN) against I/R induced renal injury has not been investigated. Hence, this study aimed to investigate the in vivo effect of XN against renal I/R injury. The rats used in this study were divided into 2 main groups of either 1) sham-operated or 2) subjected to renal I/R, in which each group was further divided into 2 subgroups: treated with oral administration of normal saline or XN (1 mg/kg) for 28 days. Renal function, histology, markers and expression levels of oxidative stress, inflammation and apoptosis were examined. The expression levels of the activated JAK-2/Stat-3 signalling pathway were also assessed. XN treatment in the sham group resulted in a normal response, as seen in the sham operated as control group. However, XN significantly improved renal function and attenuated histological changes by reducing the levels of oxidative stress and lipid peroxidation, inflammatory markers, adhesive molecules and the activity of myeloperoxidase (MPO). Concomitantly, reduced expression levels of activated caspase with a parallel decrease in JAK-1/Stat-3 phosphorylation were also noticed. In conclusion, these findings show, for the first time, a protective effect of XN against renal I/R injury, and the mechanisms of protection involve ROS scavenging and an anti-inflammatory effect mediated by the inhibition of the JAK-2/STAT-3 pathway.